Pengaruh Intellectual Capital, Kepemilikan Manajerial, Firm Size, Ukuran Komite Audit Terhadap Nilai Perusahaan - Putri Ananda; Melan Sinaga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine and analyze the effect of Intellectual Capital, Managerial Ownership, Firm Size, Audit Committee Size on Firm Value in Apparel and Luxury Goods Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) for 2019-2023. The method of determining the sample in this study using purposive sampling method and the population in this study were 22 companies, while the sample used was 13 companies. The data analysis used in this research is multiple linear regression analysis using SPSS software version 25. The results of this study indicate that intellectual capital has no effect on firm value, and managerial ownership has a positive and significant effect on firm value, then firm size and audit committee size have a negative and significant effect on firm value.